Kombinasi Metode Unsharp Masking dan Filter High Boost Dalam Meningkatkan Kualitas Video Call - Ayu Lorenza Rajagukguk (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Currently, the use of computer equipment has grown very rapidly in the community. Most people not only use it for commercial purposes, but also get information to detect diseases quickly and efficiently with computer-based applications that can help the general public to find out the causes and symptoms of the disease. For that, we need a system designed to imitate the expertise of an expert in answering questions and solving a problem, according to the knowledge of an expert that is entered into a computer system. The development of artificial intelligence technology that has occurred has allowed expert systems to be applied for their use in detecting diseases using programming languages. One of them is in providing information about various problems, especially Shigellosis disease. The expert system method used is Constraint Satisfaction Problem (CSP) which is used to deal with uncertainty in the diagnosis of Shigellosis